Aging‐Driven Composition and Distribution Changes of Electrolyte and Graphite Anode in 18650‐Type Li‐Ion Batteries. Issue 45 (30th September 2022) - Petz, Dominik; Baran, Volodymyr; Peschel, Christoph; Winter, Martin; Nowak, Sascha; Hofmann, Michael; Kostecki, Robert; Niewa, Rainer; Bauer, Michael; Müller‐Buschbaum, Peter; Senyshyn, Anatoliy
Abstract: A series of low‐temperature studies on LiNi0.80 Co0.15 Al0.05 O2 18650‐type batteries of high‐energy type with different stabilized states of fatigue is carried out using spatially resolved neutron powder diffraction, infrared/thermal imaging, and quasi‐adiabatic calorimetry. In‐plane distribution of lithium in the graphite anode and frozen electrolyte in fully charged state is determined non‐destructively with neutron diffraction and correlated to the introduced state of fatigue. An independent electrolyte characterization is performed via calorimetry studies on variously aged 18650‐type lithium‐ion batteries, where the shape of the thermodynamic signal is evolving with the state of fatigue of the cells. Analyzing the liquid electrolyte extracted/harvested from the studied cells reveals the decomposition of conducting salt to be the main driving factor for fatigue in the electrolyte degradation. Abstract : A series of non‐invasive experimental techniques is employed to characterize the state‐of‐health in a batch of differently aged cylinder‐type lithium‐ion batteries along with a simple and fast method to define the state‐of‐health of the electrolyte using its thermal response on freezing.